WILLINGNESS TO COMMUNICATE IN ENGLISH OF FIRST YEAR STUDENTS AT FELTE, ULIS, VNU - Nguyễn, Thị Hương Giang (2020)
One of the main purposes of learning a foreign language is to use it to communicate in an effective way. However, whether the EFL students are willing to use English to communicate has been a question to most of the English teachers. Given the important role of willingness to communicate (WTC) in learning English, there have been a number of studies about the level of WTC and the factors affecting WTC. This study is conducted to investigate the level of willingness to communicate (WTC) in English of EFL first year students at the University of Languages and International Studies (ULIS) and to identify the factors that influence the WTC in English of the participants. In order to find the answers to the research questions, two types of data collection instruments were used: a questionnaire and a semi-structured interview. Both the questionnaire and the interview aimed at measuring the level of WTC in English of the participants across different communication situations inside classroom and the factors that affect their WTC in class. The findings show that the WTC in English in class of the EFL first year students at ULIS is relatively high. First year students seemed to prefer initiating communication in English in group discussion to speaking in front of the whole class. Regarding the factors affecting the student’s WTC, the desire to enhance the English speaking skill is the most influential variable. In addition, some pedagogical recommendations are also provided for the purpose of encouraging students to communicate in class.